Increase in Arctic Oscillations explains most interannual variability in Russia’s wildfires - Lapenis, Andrei G.; Yurganov, Leonid N. (Frontiers in Forests and Global Change, 2023)
Over the past two decades, a conspicuous annual escalation in greenhouse gas (GHG) emissions stemming from wildfires within the boreal expanse of the Northern Hemisphere has come to light. These extensive wildfires have materialized unpredictably across a spectrum of locales and temporal spans, culminating in an unparalleled conflagration season in 2021. This article is a climatological perspective on the appraisal of carbon emissions originating from wildfires with a concurrent focus on unraveling the underlying catalysts driving the variability in wildfire occurrences. Analyzing atmospheric circulation indices prevalent in high latitudes, in conjunction with the historical record of greenhouse gas (GHG) emissions linked to Russian wildfires, demonstrates that a minimum of 50% of the variations in wildfire emissions can be attributed to shifts in the Arctic Oscillation (AO) index. Given that the AO index is influenced by the ongoing regression of Arctic Sea ice, which is driven by global warming, it can be inferred that in the foreseeable future, Russian forests might undergo a transition from functioning as carbon sinks to potentially evolving into sources of carbon emissions to the atmosphere. This trajectory is expected to gather momentum as both industrial emissions and occurrences of forest fires increase over time